Detection of highly toxic elements (lead and chromium) in commercially available eyeliner (kohl) using laser induced break down spectroscopy. (December 2015) - Gondal, M.A.; Dastageer, M.A.; Al-Adel, F.F.; Naqvi, A.A.; Habibullah, Y.B.
Abstract: A sensitive laser induced breakdown spectroscopic system was developed and optimized for using it as a sensor for the detection of trace levels of lead and chromium present in the cosmetic eyeliner (kohl) of different price ranges (brands) available in the local market. Kohl is widely used in developing countries for babies as well adults for beautification as well eyes protection. The atomic transition lines at 405.7 nm and 425.4 nm were used as the marker lines for the detection of lead and chromium respectively. The detection system was optimized by finding the appropriate gate delay between the laser excitation and the data acquisition system and also by achieving optically thin plasma near the target by establishing the local thermodynamic equilibrium condition. The detection system was calibrated for these two hazardous elements and the kohl samples under investigation showed 8–15 ppm by mass of lead and 4–9 ppm by mass of Chromium, which are higher than the safe permissible levels of these elements. The limits of detection of the LIBS system for lead and chromium were found to be 1 and 2 ppm respectively. Highlights: A LIBS system for detecting lead and chromium present in eye liner was developed. The system was optimized with different experimental and plasma parameters. Atomic transition lines Pb-1 405.7 nm and Cr-I 425.4 nm were used. The system is capable of detecting Pb and Cr levels as low as 1–2 ppm. Pb and Cr levels in the tested samples are found to be above permissible level.